Effects of non-stoichiometric RuOx thin films on the dielectric properties of BaTiO3 thin films - Kim, Y.T.; Lee, C.W. (Springer-Verlag GmbH & Company KG, Berlin, Germany, 1996)
The deconvolution process of X-ray photoemission spectra for O 1s and Ru 3d, X-ray diffraction and Rutherford backscattering spectrometry reveal that the RuOx films (x = 2.0-2.2) deposited at a O2 partial pressure less than 30% show (110)-oriented grains, whereas the RuOx films (x = 2.3-2.4) deposited at a 40-50% O2 partial pressure show amorphous and (101)-oriented grains due to the excess O interstitials and RuO3 or RuO4. These differences in the crystal phases of RuOx influence the crystal structure of BaTiO3 deposited on these RuOx bottom electrodes, resulting in a higher dielectric constant and a lower dissipation factor for tetragonal BaTiO3/RuOx (x = 2.1) than amorphous BaTiO3/RuOx (x = 2.4).
Keywords: Amorphous films; Barium titanate; Composition effects; Crystal structure; Dielectric films; Dielectric properties; Ferroelectric materials; Thin films; Partial pressure; Dielectric materials